PENGARUH HARGA, PROMOSI DAN PERSEPSI KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN DIAMOND MOBILE LEGEND PADA WEBSITE CODASHOP - Reynaldi, Reynaldi; Karla, Eva; Stevianus, Stevianus (Journal of Information System, Applied, Management, Accounting and Research, 2024)
The aim of this research is to analyze the influence of price, promotion and perceived convenience on the decision to purchase mobile legend diamonds on the Codashop website. The analysis method in this research uses quantitative primary data, the test stages carried out are: normality test, multicollinearity test, heteroscedasticity test, T test, F test, and coefficient of determination. The data used in this research used a questionnaire instrument and valid data which was collected from 100 respondents. The data collection technique used in this research is through a questionnaire. The testing tool used is SPSS version 25 software. The research results show that partially the variable Price (X1) has a sig value of 0.000 < 0.05, Promotion (X2) has a sig value of 0.000 < 0.05 and Perceived Convenience (X3) has a sig value of 0.001 < 0.05. This means that partially price, promotion and perceived convenience have a positive and significant effect on purchasing decisions. Meanwhile, simultaneous calculations obtained a sig value of 0.000 < 0.05. This means that price, promotion and perceived convenience together (simultaneously) have a positive influence on the decision to purchase Diamond Mobile Legend on the Codashop website.